The role of the class I Wnt pathway antagonist sFRP4 in colorectal cancer - Liu, Yuting; Li, Jianfeng; Qi, Jian (Digestive Medicine Research; Vol 2 (August 2019): Digestive Medicine Research, 2019)
olorectal cancer is a common malignancy in humans. Studies have shown that the development and progression of 90% of colorectal cancers are related to abnormal activation of the Wnt signaling pathways. Secreted frizzled-related protein 4 (sFRP4) is a class I antagonist of the Wnt signaling pathways, and inhibition of sFRP4 expression effectively reduces Wnt signaling activity. DNA hypermethylation of sFRP4 has been found in the early stage of colorectal cancer. However, there is still controversy surrounding the expression of sFRP4 in colorectal cancer. sFRP4 expression is related to the malignant degree, drug resistance, and invasiveness of tumors. The present article reviews the role of the sFRP4 gene, a class I antagonist of the Wnt signaling pathway, in colorectal cancer.